Contact Angles of a Brine on a Bituminous Coal in Compressed Hydrogen. Issue 8 (22nd April 2022) - Sedev, Rossen; Akhondzadeh, Hamed; Ali, Mujahid; Keshavarz, Alireza; Iglauer, Stefan
Abstract: Hydrogen storage is a main issue in the establishment of a hydrogen economy. Geo‐storage could be a viable solution if hydrogen could be injected into and withdrawn from suitable geological formations, reversibly and reliably. Rock wettability is a major factor as it affects injectivities, withdrawal rates, storage capacities, and containment security. We report here the contact angles of a brine on the surface of a bituminous coal in a pressurized hydrogen atmosphere. Under realistic geo‐storage conditions the coal surface was weakly water‐wet. Hydrogen pressure increased brine contact angles at 25°C but did not have an impact at 50 or 70°C. We present a thermodynamic model that describes the observed behavior. Our results would support the development of large‐scale geo‐storage technologies for hydrogen. Plain Language Summary: The wide use of hydrogen as a clean fuel will require significant storage capacities. Above ground facilities are expensive and the possibility of underground storage must be considered. It is technologically feasible as it is already practiced with natural gas and carbon dioxide. Wettability, which reflects the interactions between the liquids, gases and rocks, plays an important role in understanding and controlling the behavior and movement of gases inside rocks partially filled with brine. We provide here measurements of the brine wettability of coal in the presence of hydrogen. These results will feed into the development of new technologies for underground storage of hydrogen. Key Points: The surface of a bituminous coal is weakly water‐wet in a hydrogen environment Hydrogen pressure increases the brine contact angles at 25°C but has no impact at 50 or 70°C Wettability changes are attributed to the hydrogen adsorption on the coal surface